2012
DOI: 10.1111/j.1423-0410.2012.01591.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial skin flora and contamination of blood components: do we defer blood donors wisely?

Abstract: This study shows that our current guidelines for deferral of blood donors with skin disorders effectively identifies individuals with a high number of bacteria on their skin, as well as S. aureus carriers. However, deferral due to skin disorders had only a minor impact on blood product contamination when compared to other actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The association of high colonisation rates of S. aureus with atopic dermatitis is well known, and a recent study reported that among 74 eczema colonised patients, all but four harboured related S. aureus strains at three sampling sites [16]. In Finland, dermal disorders or a skin infection results in donor deferral as the number of bacteria at the VP site was shown to be significantly higher in individuals with such conditions compared with controls [17]. Two of the three apheresis donors implicated in our near-miss incidents reported nonhealing skin lesions on the leg and nose, respectively; the first donor was culture negative at the skin site but both donors had nasal carriage of S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…The association of high colonisation rates of S. aureus with atopic dermatitis is well known, and a recent study reported that among 74 eczema colonised patients, all but four harboured related S. aureus strains at three sampling sites [16]. In Finland, dermal disorders or a skin infection results in donor deferral as the number of bacteria at the VP site was shown to be significantly higher in individuals with such conditions compared with controls [17]. Two of the three apheresis donors implicated in our near-miss incidents reported nonhealing skin lesions on the leg and nose, respectively; the first donor was culture negative at the skin site but both donors had nasal carriage of S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Finland, Tanzania, and Morocco showed frequencies of S. aureus and Gramnegative bacteria between 7%-16.74% and 13.73%-41.2% of blood donors, respectively. 8,19,20 Of note, the Tanzanian study sampled skin from healthy participants (no blood donors) at the sterno-clavicular joint, which is categorized as sebaceous and a typical habitat for Gram-positive skin bacteria, whereas the antecubital fossa is categorized as moist and harbors Gram-negative bacteria. 16 In the Moroccan study, participants were voluntary blood donors, onethird of them trainees at the study hospital.…”
Section: Discussionmentioning
confidence: 99%
“…They were taken under non-sterile conditions, and it is possible that common contaminants like S . aureus , coagulase-negative staphylococci and Pseudomonas genera may have originated from the bacterial skin flora [8, 10].…”
Section: Discussionmentioning
confidence: 99%